Ethnomycology Study: Mushrooms Traditionally Utilized by the Malay Tribe in Lorong Village, Sambas Regency, West Kalimantan - Faturrahman, Mas Akhbar; Yeni, Laili Fitri (Department of Mathematics and Science Education, Faculty of Teacher Training and Education, University of Mataram. Jurnal Pijar MIPA colaborates with Perkumpulan Pendidik IPA Indonesia Wilayah Nusa Tenggara Barat, 2024)
Mushrooms play a role in human life. People generally utilize mushrooms traditionally as food and medicine. This particular ethnomycology study aims to determine the species of mushrooms used by the Malay Tribe in Lorong Village, specifically as food and medicine, with the background that it is necessary to invent and document the mushrooms used by the community, and the lack of research related to ethnomycology has been conducted. The study was conducted in May 2022. Descriptive qualitative research was utilized using interview techniques based on snowball sampling and cruise methods to search the mushrooms. Interviews were conducted with ten critical informants aged 33 to 85 years old. The results show that the Malay Tribe in Lorong Village used seven mushroom species for consumption and as medicines. The seven mushrooms were from Marasmiaceae, Physalacriaceae, Schizophyllaceae, Auriculariaceae, Dacrymycetaceae, Sarcoscyphaceae, and Xylariaceae. Mushroom species used for food are Marasmiellus sp., Oudemansiella sp., Schizophyllum sp., Auricularia sp., Dacrymyces sp., and Cookeina sp., while the mushroom species used for medicine are Daldinia sp. Mushroom species utilized as food are generally made as food mixtures, such as soup, pepes, bubur pedas, stir-fry, and bakwan. Mushroom species that are utilized as medicines are used to treat boil.